Methods of wedge dehydration of biological fluids. - Markevich, V. E.; Kirilenko, E. A.; Petrashenko, V. A.; Zablotskaya, T. U.; Bilokon, T. A. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Investigation of facies of biological fluids is utilized for the diagnostics of different disease in ophthalmology, dentistry, oncology, gerontology, neurology, surgery, obstetrics and gynecology, tuberculosis, neonatology, nephrology. Objective. To familiarize a wide range of medical specialists with a diagnostic technology of investigation of biological fluids using the method of wedge dehydration. Methods. On the fat-free slide positioned horizontally a droplet of biological fluid of 0,01-0,02 ml is added. Within 18-24 hours at a temperature of 20-25 °C and a relative humidity of 65-70% the sample dry and is investigated with the help of microscope. Results. During dehydration a number of processes leading to the formation of the facies with a certain structure depending on the type of biological fluid are observed. Facia has 3 zones: 1 – central – the zone of the crystal structures, 2 – the transitional zone, amorphous and 3 – peripheral. The process of recognition of facies structures occurs qualitatively, not quantitatively and depends on the experience and skills of the image "reading" of the assistant. These deficiencies can be corrected by creation an automated image analysis system. Conclusions. We demonstrated the possibility of computer program to implement an automated processing of facies of biological fluids.